High Altitude Medicinal Plant Diversity and Conservation Strategies in Uttarakhand: An overview - Panwar, G. S.; Manikandan, R.; Kumar, Puneet; Srivastava, S. K. (Indian Forester, 2018)
The study reveals that there are 1650 species of ethno-medicinal plants recorded from the state of Uttarakhand, out of these around 701 species are high altitude medicinal plants and among these high altitude regions about 161 species are under various threatened categories.